Prefrontal Compensatory Engagement in TBI is due to Altered Functional Engagement Of Existing Networks and not Functional Reorganization - Turner, Gary R.; McIntosh, Anthony R.; Levine, Brian (Frontiers in Systems Neuroscience, 2011)
Functional neuroimaging studies of traumatic brain injury (TBI) have demonstrated altered neural recruitment, specifically within prefrontal cortex (PFC). This is manifest typically as increased recruitment of homologous regions of PFC (e.g. right ventrolateral PFC during performance of a verbal working memory task, possibly in response to damage involving the left PFC). The behavioural correlates of these functional changes are poorly understood. We used fMR imaging and multivariate analytic methods to investigate changes in spatially distributed activity patterns and their behavioural correlates in a sample of TBI patients with diffuse axonal injury (DAI, but without focal injury) and matched healthy controls. Participants performed working memory tasks with varying memory load and executive demand. We identified networks within left and right PFC that uniquely and positively correlated with performance in our control and TBI samples respectively, providing evidence of compensatory functional recruitment. Next we combined brain-behaviour and functional connectivity analyses to investigate whether compensatory brain changes were facilitated by functional reorganization (i.e. recruitment of brain regions not engaged by our control sample) or altered functional engagement (i.e. differential recruitment of similar brain regions between the two groups based on task demands). In other words, does altered recruitment represent the instantiation of novel neural networks to support working memory performance after injury or the unmasking of extant, but behaviourally latent, functional connectivity? Our results support an altered functional engagement hypothesis. Areas within PFC that are normally coactivated during working memory are behaviorally-relevant at an earlier stage of difficulty for TBI patients as compared to controls. This altered functional engagement, also evident in the aging literature, is attributable to distributed changes owing to significant DAI.